Cardiovascular magnetic resonance imaging and clinical performance of somatostatin receptor positron emission tomography in cardiac sarcoidosis. (12th December 2017) - Pizarro, Carmen; Kluenker, Folke; Dabir, Darius; Thomas, Daniel; Gaertner, Florian C.; Essler, Markus; Grohé, Christian; Nickenig, Georg; Skowasch, Dirk
Abstract: Aims: Cardiac affection constitutes a major limiting condition in systemic sarcoidosis. The primary objective of this study was to investigate the persistence rate of cardiac sarcoid involvement by cardiovascular magnetic resonance (CMR) imaging in patients diagnosed with cardiac sarcoidosis (CS). Moreover, we examined the additional insights into myocardial damage's characteristics gained by somatostatin receptor scintigraphy. Methods and results: In a pilot study, we had previously identified cardiac involvement—diagnosed by CMR imaging—to be present in 29 of 188 patients (15.4%) with histologically proven, extra‐CS. Out of these initial 29 CS‐positive patients, 27 patients (49.9 ± 11.8 years, 59.3% male) were presently re‐examined and underwent a second CMR study and complementary standard clinical testing. Somatostatin receptor scintigraphy using the ligand 68 Ga‐DOTATOC was additionally performed when clinically indicated (17 patients). Within a median follow‐up period of 2.6 years, none of the initial 29 patients deceased or experienced aborted sudden cardiac death. However, two patients developed third‐degree atrioventricular block that required device therapy. Among the 27 re‐examined CS patients, pathological CMR findings persisted in 14 of 27 patients (51.9%). CS remission was primarily due to a resolution of acute inflammatory processes. 68 Ga‐DOTATOC positron emission tomography/computed tomography (PET/CT) identified one patient with regions of raised tracer uptake that concorded with acute inflammatory changes, as assessed by CMR; this patient received no immunosuppressive medication at the time of PET/CT execution. Conclusions: Within follow‐up, CS persisted in barely half the patients, and the patients were not afflicted with cardiac death. Additional 68 Ga‐DOTATOC PET/CT allowed for visualization of acute myocardial inflammation.